Breaking Away From Charisma? The Celebrity Industry's Contradictory Connection to Charismatic Authority. Issue 4 (1st June 2017) - Hendriks, Eric Cornelis
Abstract : Some scholars label celebrities as "charismatic, " while others avoid that Weberian term, deeming it inappropriate in the context of celebrity culture. None, however, offers a systematic account of the relationship between Weberian charisma and celebrity. To this task, this article moves beyond the semantics toward a systematic analysis and comparison of the logics guiding charismatic and celebrity dynamics. I argue that charisma and celebrity represent distinct and even partly contradictory logics of social distinction, but that they nonetheless substantially intertwine and coextend in society, which renders their interaction ambiguous, conflictual, and creative of new social forms. This social‐ontological conceptualization provides the now‐lacking theoretical foundation for empirical studies into the many complex interactions between charismatic and celebrity dynamics throughout society.